Local, Regional and National Responses for Medical Management of a Radiological/Nuclear Incident. Issue 1 (1st January 2013) - Dainiak, Nicholas; Skudlarska, Beata; Albanese, Joseph
Radiological and nuclear devices may be used by terrorists or may be the source of accidental exposure. A tiered approach has been recommended for response to a terrorist event wherein local, regional, state and federal assets become involved sequentially, as the magnitude in severity of the incident increases. State-wide hospital plans have been developed and published for Connecticut, New York and California. These plans address delineation of responsibilities of various categories of health professionals, protection of healthcare providers, identification and classification of individuals who might have been exposed to and/or contaminated by radiation and, in the case of Connecticut response plan, early management of victims. Regional response programs such as the New England Regional Health Compact (consisting of 6 member states) have been developed to manage consequences of radiation injury. The Department of Homeland Security is ultimately responsible for managing both health consequences and the crisis. Multiple US national response assets may be called upon for use in radiological incidents. These include agencies and programs that have been developed by the Department of Energy, the Environmental Protection Agency and the Department of Defense. Coordination of national, regional and state assets with local response efforts is necessary to provide a timely and efficient response.